SAFEGUARDING THE EUROPEAN POND TURTLE: CONSERVATION STRATEGIES IN TÜRKIYE - Dinçer , Ayaz; Bayrakcı , Yusuf; Çiçek, Kerim (Actual problems and prospects of the study of the fauna, 2024)
The European Pond Turtle (Emys orbicularis) has experienced a significant population decline across its range due to habitat loss, climate change, and human activities. This review examines the factors contributing to its decline, such as habitat degradation from agricultural practices, climate shifts, and population fragmentation, which limits gene flow and increases the risk of local extinctions. Conservation efforts, including habitat restoration, legal protections under the Natura 2000 framework, and population management techniques, have been implemented with varying success. In Türkiye, a subspecies, Emys orbicularis eiselti, faces critical endangerment, with fewer than 100 mature individuals remaining. Conservation strategies must prioritize habitat connectivity and address both aquatic and terrestrial habitat needs. A multifaceted, adaptive approach that incorporates continued research and landscape management is essential for the long-term survival of the species.